Diverse HIV epidemics among people who inject drugs in Thailand: Evidence from respondent-driven sampling surveys in Bangkok and Chiang Mai. (1st March 2015) - Prybylski, Dimitri; Manopaiboon, Chomnad; Visavakum, Prin; Yongvanitjit, Kovit; Aramrattana, Apinun; Manomaipiboon, Parnrudee; Tanpradech, Suvimon; Suksripanich, Orapin; Pattanasin, Sarika; Wolfe, Mitchell; Whitehead, Sara J.
Highlights: We conducted respondent-driven sampling (RDS) surveys among people who inject drugs (PWID) in Bangkok and Chiang Mai, Thailand. Overall HIV prevalence was higher among PWID in Bangkok than Chiang Mai. PWID in Bangkok appear to be an aging cohort with long-standing HIV infections. PWID in Chiang Mai appear to have acquired their infections more recently. In Chiang Mai PWID were younger and had higher levels of recent risk behaviors with lower intervention exposure. Abstract: Background: Thailand's long-standing HIV sero-sentinel surveillance system for people who inject drugs (PWID) is confined to those in methadone-based drug treatment clinics and representative data are scarce, especially outside of Bangkok. Methods: We conducted probability-based respondent-driven sampling (RDS) surveys in Bangkok ( n  = 738) and Chiang Mai ( n  = 309) to increase understanding of local HIV epidemics and to better inform the planning of evidence-based interventions. Results: PWID had different epidemiological profiles in these two cities. Overall HIV prevalence was higher in Bangkok (23.6% vs. 10.9%, p  < 0.001) but PWID in Bangkok are older and appear to have long-standing HIV infections. In Chiang Mai, HIV infections appear to be more recently acquired and PWID were younger and had higher levels of recent injecting and sexual risk behaviors with lower levels of intervention exposure. Methamphetamine was the predominant drug injected in both sites and polydrug use was common although levels and patterns of the specific drugs injected varied significantly between the sites. In multivariate analysis, recent midazolam injection was significantly associated with HIV infection in Chiang Mai (adjusted odds ratio = 8.1; 95% confidence interval: 1.2–54.5) whereas in Bangkok HIV status was not associated with recent risk behaviors as infections had likely been acquired in the past. Conclusion: PWID epidemics in Thailand are heterogeneous and driven by local factors. There is a need to customize intervention strategies for PWID in different settings and to integrate population-based survey methods such as RDS into routine surveillance to monitor the national response.